Legal Sanctions Against Notaries Who Violate Obligations and Prohibition of the Law on the Position of A Notary - Fitria Dewi Navisa (Lambung Mangkurat Law Journal, 2024)
Law Number 2 of 2014 concerning the Position of Notaries (UUJN) regulates mutual agreements and statutory regulations against Notaries who abuse the commitments and prohibitions as intended in Articles 16 and 17 UUJN, but criminal authority is not regulated in UUJN, therefore its use criminal sanctions In addition, there is no action against the joint authorization component related to the cancellation of authentic deeds in the UUJN. This authority is represented in Article 7 paragraph (2), Article 16 paragraph (11 and 13), Article 17 paragraph (2), Article 19 paragraph (4), Article 32 paragraph (4), Article 37 paragraph (2), Article 54 paragraph (2) and Article 65 UUJN. Criminal sanctions are not represented, however a Notary can be punished according to the provisions of the Criminal Code, considering that the appointment of a Notary is in accordance with the definition of burglary as regulated in the UUJN, code of ethics and corrective code. . Second, the component of using joint power relating to the deletion of a valid deed into a private deed must go through a joint lawsuit process in a general court held by the association whose name is listed in the deed and which suffers negative consequences. as a result of these actions